Eoigenetic remodeling of mesenchymal stem cell (msc), by targeting specific micrornas to induce long term neurogenesis: an in vitro analysis of msc plasticity - Hasnan, Jaafar (Pusat Pengajian Kesihatan, 2015)
Recently, there has been an increasing interest in MSCs plasticity and their potential to transdifferentiate into neural lineages. To have an in-depth understanding of optimal transdifferentiation and its microenvironment, we have transdifferentiated MSCs in different combinatorial treatment of growth factors. Based on previous studies about the roles of IGF-1 in the laboratory, we hypothesized that IGF-1 can provide an optimal microenvironment for long-term maintenance and efficient neural induction. Here, we also analysed the roles of differential microRNAs in the transdifferentiation of MSC into neural lineage in the presence of IGF-1. Neuronal induction was carried under four different micorenvironments: (A) EGF/bFGF, (B) EGF/bFGF/IGF, (C) EGF/bFGF/LIF, (D) EGF/bFGF/BDNF and (E) without growth factor as negative control. Neurospheres formed were characterized by immunofluorescence staining against nestin and the expression was measured by flow cytometry. The cell proliferation and apoptosis was also studied by MTS and Annexin V assay respectively at three different time intervals (24 hours, Day 3 and Day 5). All groups showed significant higher in nestin expression as compared to negative control group. Interestingly, IGF-1 treated group shows better enhancement in cell proliferation and cell survival efficiency. To delineate the exact miRNA signatures in IGF-1 treated sample, we performed miRNAs profiling and analyzed using Genespring software. Among the 2t miRNAs differentially expressed, let-7b, miR-18ta, and miR-26a were found to be specially espressed in IGF-1 treated group. All of them are involved in apoptosis suppression, improve cell proliferation and promote neuronal differentiation. Our results demonstrate that IGF-1 enhanced cell proliferation and suppressed cell death by triggering the expression of specific miRNAs. This information will be beneficial for improving both cell-based and cell-free therapy of neurodegenerative diseases in the long run.